Urodynamic assessment of orthotopic urinary diversions - Palleschi, Giovanni; Cardi, Antonio; Falsaperla, Mario (Frontiers in Urology, 2022)
Orthotopic neobladder represents the best option for bladder reconstruction in terms of body image preservation and postoperative QoL for patients submitted to radical cystectomy. This technique offers also good short-term and logn-term functional outcomes. Nowadays, ileal orthotopic neobladder is the the bladder reconstruction of choice for both sexes of because there is large evidence of its superiority respect to other techniques in terms of surgical and functional results. Complications may develop during the follow-up, therefore clinical and instrumental adequate assessment is mandatory to early recognize alterations of neobladder function thus to prevent damages to the reservoir itself and to the kidney function, which can affect patients’ quality of life. Literature has shown that urodynamics and videourodynamics have significantly contributed to assess the functional aspects of ileal neobladders since the beginning of their use in patients submitted radical cystectomy, helping surgeons to improve the technical aspects of the procedure. After the preliminary results, many groups have observed that urodynamics and videourodynamics are the best tools to evaluate morphology and function of ileal neobladders. These diagnostic methods help to correctly diagnose the cause of altered neobladder function simultaneously providing anatomical informations that can be related to clinical signs and symptoms. Recent studies have confirmed the usefullness of these instruments also in patients with ileal neobladder achieved by laparoscopic and robotic approach, confirming the higher diagnostic value also respect to modern imaging techniques, as three dimensional computed tomography and magnetic resonance.